The Effectiveness of Foot Massage on Reducing Intradialytic Blood Pressure in the Hemodialysis Room of RS.TK. II Pelamonia Makassar - Andi Wahyuni; Aminullah; Nursamsi; Muhammad Abu; Hayyu sitoresmi (Comprehensive Health Care, 2023)
Chronic Kidney Disease (CKD) is a health problem with an increasing prevalence every year. Deaths caused by chronic kidney failure increased by 31.7% over the last 10 years and became the 3rd leading cause of death in the world. The number of patients with chronic kidney failure in the world exceeds 500 million with 1.5 million undergoing hemodialysis. Objective: The purpose of this study was to determine the effectiveness of foot massage in reducing intradialytic blood pressure given to patients with chronic kidney failure who were in the hemodialysis room of the hospital. kindergarten. II Pelamonia Makassar. This type of research is quasi-experimental with a one-group pre-post-test design to compare the results of the intervention before and after giving a foot massage to the decrease in intradialytic blood pressure in the Hemodialysis Room of the Hospital. kindergarten. II Pelamonia Makassar. Results: Statistical test results showed that foot massage was effective in reducing intradialytic blood pressure (Ï=0.00). Conclusion: this study shows that foot massage is effective for reducing intradialytic blood pressure, both systolic and diastolic blood pressure.